In Vitro Safety Study on the Use of Cold Atmospheric Plasma in the Upper Respiratory Tract - Karrer, Sigrid; Unger, Petra; Gruber, Michael; Gebhardt, Lisa; Schober, Robert; Berneburg, Mark; Boßerhoff, Anja Katrin; Arndt, Stephanie (Cells, 2024)
Cold atmospheric plasma (CAP) devices generate reactive oxygen and nitrogen species, have antimicrobial and antiviral properties, but also affect the molecular and cellular mechanisms of eukaryotic cells. The aim of this study is to investigate CAP treatment in the upper respiratory tract (URT) to reduce the incidence of ventilator-associated bacterial pneumonia (especially superinfections with multi-resistant pathogens) or viral infections (e.g., COVID-19). For this purpose, the surface-microdischarge-based plasma intensive care (PIC) device was developed by terraplasma medical GmbH. This study analyzes the safety aspects using in vitro assays and molecular characterization of human oral keratinocytes (hOK), human bronchial–tracheal epithelial cells (hBTE), and human lung fibroblasts (hLF). A 5 min CAP treatment with the PIC device at the “throat” and “subglottis” positions in the URT model did not show any significant differences from the untreated control (ctrl.) and the corresponding pressurized air (PA) treatment in terms of cell morphology, viability, apoptosis, DNA damage, and migration. However, pro-inflammatory cytokines (MCP-1, IL-6, and TNFα) were induced in hBTE and hOK cells and profibrotic molecules (collagen-I, FKBP10, and αSMA) in hLF at the mRNA level. The use of CAP in the oropharynx may make an important contribution to the recovery of intensive care patients. The results indicate that a 5 min CAP treatment in the URT with the PIC device does not cause any cell damage. The extent to which immune cell activation is induced and whether it has long-term effects on the organism need to be carefully examined in follow-up studies in vivo.
CRIS-Team Scopus Importer:2024-09-20
Keywords: cold atmospheric plasma (CAP); human bronchial–tracheal epithelial cells (hBTE); human lung fibroblasts (hLF); human oral keratinocytes (hOK); plasma intensive care (PIC); pressurized air (PA); upper respiratory tract (URT)